Bebês e professora em ações interativas de cuidado/educação na educação infantil : o banho e a alimentação em foco - Rodrigues, Thamisa Sejanny de Andrade (2019)
Teaching with babies has specificities that constitute the movement of interaction, experiences and interactive actions with / among social actors in the daily education of children. The main objective of this research is to understand how the actions of care / education between infants and their teacher are constituted, in the moments destined to the personal care, in feeding and bathing situations. Specifically, it was sought to observe the interactive actions of infants and their teacher, in order to analyze how these actions constitute as educational practices in the institution of Early Childhood Education. From this, and considering the moments of feeding and bathing, was listed as the focus of analysis: 1) the sociocommunication actions used by the babies in occasions of interactions with their teacher; 2) the interactive actions initiated and maintained by the teacher in face of the social (re) actions expressed by the babies; 3) the ways that infants represent acts of personal care received during bathing and feeding in interaction with the couple of age. The study has a qualitative approach and a descriptive exploratory character. The subjects participating in the present investigation are 7 (seven) babies and a teacher, members of the age group called nursery 1, of a municipal institution of Early Childhood Education located in Nossa Senhora do Socorro / SE. Therefore, the main theoretical sources composed the studies that are included in the call Pedagogy(s) of Childhood(s). As data generation instruments, participant observation, recording in field diary, photographs and video recordings of moments for feeding and bathing are used. The data were analyzed based on observation, selection and description of interactive episodes that were produced in the articulation between the empirical data emerging from the study in the light of the chosen theoretical reference. We show that moments related to bathing and feeding are usually marked by significant interactions between infants and their teacher, constituting important educational practices for the integral development of infants, which are materialized in actions that go beyond dietary and bodily hygiene needs, which are also important, but which in this study are revealed as moments of social, cultural and affective learning that integrate the indissociability of caring / educating the child. Interactive actions between infants and older mates reveal that they are powerful in the learning they take on the personal care they receive during bathing and feeding.